Between batumes and swamps: the life of the isqueiros of the North Pantanal (Research, Society and Development, 2022)
This experience report is the result of periods of experience in environments of live bait collection and in camps of artisanal professional fishermen categorized as isqueiro (live bait catchers), in the North Pantanal region, aiming to know and experience this activity. The experience took place at two collection points along the Paraguay River, 75 km upstream from the urban center of Cáceres-MT, and at another point further away, about 250 km. The activities took place in February and July 2022. During this period of experience, the techniques used to capture live baits, the social organization, and the challenges faced by these actors in the development of the activity were observed. After this period, it is observed that there is a vertical social organization in which knowledge is passed from generation to generation; the bait catchers carry out the activities in pairs, due to the risks involved in the work, both in the collection of live baits and the capture of termites to supply the traps. There are existing conflicts related to the capture of termites to capture live baits since there is no land in several regions where catchers are camped and they even use private areas to develop their activities.